Transforming growth factor-beta 1, vascular endothelial growth factor, and bone morphogenic protein-7 expression in tacrolimus-induced nephrotoxicity in rats - TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2006)
The aim of our study was to investigate transforming growth factor (TGF)-beta 1, vascular endothelial growth factor (VEGF), and bone morphogenic protein-7 (BMP-7) expression in the rat model of chronic tacrolimus (TAC) toxicity compared to healthy controls. Seventeen male Wistar rats were divided into two groups: group 1 animals were healthy controls and Group 2 animals were treated with TAC (1 mg/kg per day intraperitoneally for 8 weeks). At the end of the study period the animals were sacrificed following renal function studies including blood urea nitrogen (BUN), serum creatinine, and creatinine clearance, and renal tissues were examined by light microscopy for the findings of tacrolimus toxicity, specifically for afferent arteriolopathy and interstitial fibrosis. TGF-beta 1, VEGF, and BMP-7 expression were assessed by semiquantative scoring of the immunohistochemically stained specimens. Mean TAC levels were 5.53 +/- 2.38 ng/mL in group 2. BUN, creatinine levels, and creatinine clearance were 57.99 +/- 11.13 vs 39.49 +/- 5.64 mg/dL; 0.60 +/- 0.16 vs 0.65 +/- 0.09 mg/dL; 0.97 +/- 0.39 vs 1.17 +/- 0.32 mL/min in group 2 versus group 1. Only the BUN level was significantly higher in group 2 compared to group 1. Afferent arteriolopathy and interstitial fibrosis were significantly increased in group 2 compared to group 1. TGF-beta 1 and VEGF expression was significantly increased while BMP-7 expression was significantly decreased in group 2 versus group 1. In conclusion, our findings suggest that TAC-induced nephrotoxicity is associated with increased TGF-beta 1 and VEGF and decreased BMP-7 expression.
Keywords: CYCLOSPORINE; FK506